A Qualitative Exploration on the Perception of Gangs and Gangsterism in Malaysia - Sharon Wilson; Thanaseelan Rajasakran; Santhidran Sinnappan; Thinavan Periyayya (Universiti Sains Islam Malaysia, 2025)
Sains Insani, Volume 9 Issue 2 Page (362–376)